Modifikasi Permukaan Elemen Peredam Bising dengan Profil Berbentuk Prisma - Julius Indra Kusuma; H Harjana; Iwan Yahya (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2016)
The influence of surface modification by using prism shaped profile on the sound absorption of absorber element was investigated experimentally. A prime number based configuration of the two types opened and closed type rism shaped profile inclusion was tested by using impedance tube according ASTM E1050 standard. The result shows that sound absorption at low frequency band below 200 Hz increased with the increasing of closed prism number. It is related to the coupling effect between the cavities of the absorber element and the prisms that changes reactance of the coupled structure. In the other side, a half wave resonance like effect occur on the use of opened prisms inclusion, which is increase the sound absorption performance at mid to high frequency range between 800 Hz to 1.25 kHz.